Cardiac Conduction System Pacing: A Comprehensive Update - Vijayaraman, Pugazhendhi; Chelu, Mihal G; Curila, Karol; Dandamudi, Gopi; Herweg, Bengt; Mori, Shumpei; Jastrzebski, Marek; Sharma, Parikshit S; Shivkumar, Kalyanam; Tung, Roderick; Upadhyay, Gaurav; Vernooy, Kevin; et al. (JACC. Clinical electrophysiology, 2023)
The field of cardiac pacing has changed rapidly in the last several years. Since the initial description of His bundle pacing targeting the conduction system, recent advances in pacing the left bundle branch and its fascicles have evolved. The field and investigators' knowledge of conduction system pacing including relevant anatomy and physiology has advanced significantly. The aim of this review is to provide a comprehensive update on recent advances in conduction system pacing.
Keywords: elektrokardiografie; Bundle of His; Cardiac Conduction System Disease; His bundle pacing; Hisův svazek; left bundle branch pacing; conduction system pacing; nemoci převodního systému srdečního; převodní systém srdeční; Electrocardiography; clinical trials; Humans; Bundle-Branch Block; Heart Conduction System; Cardiac Resynchronization Therapy; blokáda Tawarova raménka; cardiac resynchronization therapy; srdeční resynchronizační terapie; lidé